The Effect of Propolis Trigona sp. Water Extract from North Lombok on Blood Sugar Levels in Vivo - Muhammad Naufal Farras Ananta; Imasayu Nuralyza; Ani Fatin Humaira; Salwa Sausan; Lalu Husnul Hidayat; Raisya Hasina; Iman Surya Pratama; Yayuk Andayani; Siti Rahmatul Aini (Postgraduate, University of Mataram, 2024)
Propolis has been touted for its ability to regulate blood sugar levels in diabetes, but the effectiveness can vary depending on the region. A study was conducted to investigate the effect of propolis Trigona sp. water extract on blood sugar levels in vivo. The mice were divided into three groups, with four mice in each group. The positive control group received a 5 mg/kgBW glibenclamide suspension, the negative control group was given a 0.25% CMC-Na suspension, and the treatment group was administered with water extract of propolis at a dose of 300 mg/kgBW. All groups were induced with a 20% D-glucose solution intraperitoneally, and blood sugar levels were measured at 15, 30, 60, 90, and 120 minutes via the tail vein. The blood sugar data was analyzed and presented descriptively. The Mann-Whitney statistical analysis was used to determine the results, revealing that the water extract of propolis at 300 mg/kgBW did not have a significant effect on reducing blood sugar levels in animals induced by a 20% D-glucose solution, with a significance value (p < 0.05).